Fuzzy control in manufacturing systems - Wang, Hong Guang (1997)
Discusses manufacturing system control and fuzzy control concepts, which supports the fuzzy set theory and fuzzy logic theory. Applies fuzzy control concepts to simulation models that analyze performance in terms of high production and constant short lead times, under resource failures and demand variations.